2010
DOI: 10.1002/art.27267
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte C3d and C4d for monitoring disease activity in systemic lupus erythematosus

Abstract: Objective-Disease activity in systemic lupus erythematosus (SLE) is typically monitored by measuring serum C3 and C4. However, these proteins have limited utility as lupus biomarkers, because they are substrates rather than products of complement activation. The aim of this study was to evaluate the utility of measuring the erythrocyte-bound complement activation products, erythrocyte-bound C3d (E-C3d) and E-C4d, compared with that of serum C3 and C4 for monitoring disease activity in patients with SLE.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 23 publications
4
67
1
Order By: Relevance
“…In a multivariable analysis of patients with SLE, E-C4d was significantly associated with the Systemic Lupus Activity Measure (SLAM) and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) after adjusting for serum C3, C4 and anti-dsDNA antibodies [20]. Study on E-C4d from Taiwan demonstrated the same results and found that E-C4d had limited value in monitoring disease activity in SLE patients with hemolytic anemia [21].…”
Section: C4d Binding To Blood Cells In Sle Patientsmentioning
confidence: 74%
See 1 more Smart Citation
“…In a multivariable analysis of patients with SLE, E-C4d was significantly associated with the Systemic Lupus Activity Measure (SLAM) and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) after adjusting for serum C3, C4 and anti-dsDNA antibodies [20]. Study on E-C4d from Taiwan demonstrated the same results and found that E-C4d had limited value in monitoring disease activity in SLE patients with hemolytic anemia [21].…”
Section: C4d Binding To Blood Cells In Sle Patientsmentioning
confidence: 74%
“…Peripheral free C4d Plasma Monitor disease activity; predict disease flare [12,13] Serum Monitor disease activity [14] Plasma No correlation with SLE during pregnancy [15] C4d binding to blood cells E-C4d Diagnose SLE; monitor disease activity [18,20,31] R-C4d Monitor disease activity [24] P-C4d Diagnose SLE; monitor disease activity; marker for venous thrombosis in SLE; associated with all-cause mortality and ischemic stroke [25][26][27][28] T/B-C4d Diagnose SLE; monitor disease activity [29][30][31] C4d deposition in tissues…”
Section: Potential Clinical Applications Referencesmentioning
confidence: 99%
“…However, no direct comparison with a commercial assay was done for the patient samples used in the present study. Another promising approach is the measurement of C4d bound to the surface of various blood cells, such as erythrocytes, reticulocytes, and platelets [23][24][25][26]. However, the drawback of this methodology is that it is work-intensive and requires advanced equipment.…”
Section: C4dmentioning
confidence: 99%
“…However, complement activation occurs in other comorbidities such as infection, and complement activation products have low specificity, providing only a rough estimate of disease activity in SLE [70]. Recently, many studies demonstrated that cell-bound complement activation products, such as E-C4d and B-C4d, are potential markers for lupus diagnosis or evaluation of disease activity [71,72]. These cell-bound complement activation products are determined using flow cytometry.…”
Section: Complement Activation Productsmentioning
confidence: 99%